PENERAPAN LEMBAR KERJA MURID (LKM) BERBASIS GROWTH MINDSET UNTUK MENINGKATKAN HASIL BELAJAR MURID KELAS III - Tasari; Salsabila, Khairinnisa; Irvan, Khoirul; Perdana Dharma Fortuna, Kurnia; Nur Kholiq, Mohamad; Nadirin, Muhamad; Aswari, Rani; Wijayanti, Septiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This Classroom Action Research aims to improve the learning outcomes of third-grade students at SD Negeri 1 Banyuripan through the implementation of Growth Mindset-based Student Worksheets on the topic of Data Collection and Presentation. The research was motivated by the students’ low learning outcomes, in which only 2 out of 25 students (8%) met the Minimum Passing Criteria, as well as the presence of psychological factors in the form of a fixed mindset that caused students to lack self-confidence, fear making mistakes, and give up easily when facing learning difficulties. The study employed the Kemmis and McTaggart model, implemented over two cycles, encompassing the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 25 third-grade students at Banyuripan State Elementary School 1. Data were collected through achievement tests at the end of each cycle and then analyzed using quantitative descriptive methods. The results showed an improvement in learning outcomes in each cycle. In Cycle I, 15 out of 25 students (60%) achieved learning mastery with a class average score of 72. After instructional improvements were implemented in Cycle II, all students (25 students) achieved learning mastery, with the class average score rising to 88—representing a 100% mastery rate (a 40% increase from Cycle I). This improvement was also accompanied by growth in the ability to collect and present data (from 84% to 93%), problem-solving skills (from 64% to 81%), and self-awareness regarding challenges (from 77% to 95%). Thus, the implementation of Growth Mindset-Based Student Worksheets can improve learning outcomes, as evidenced by the increase in each indicator across every cycle.